Desempenho clínico de um sistema de resina composta e adesivo à base de silorano em restaurações classe I: estudo controlado e randomizado - Carolina Dolabela Leal (2014)
The aim of this split-mouth clinical study was to compare the performance of a silorane-based resin composite and adhesive system with a methacrylate-based system in class I restorations. Fifty-one individuals received at least one pair of restorations, which were randomly allocated to the test (Filtek P90 / Silorane Adhesive System, 3MESP) or control (Filtek P60 / Adper SE Plus, 3MESPE) groups. A single operator performed all restorations, following the protocols. After one week, they were finished, polished and independently assessed by two trained, blinded examiners (kW 0.7), using the modified USPHS criteria. The Wilcoxon test compared the frequencies of Alpha, Bravo and Charlie in the test and control groups in each of the evaluation periods: baseline, 12, 24 and 48 months. And the Friedman test, followed by Bonferroni correction (p <0.0125), compared the groups separately, in all evaluation periods. Results: No statistically significant differences between groups were found in the evaluation periods (p> 0.05). No significant differences were found comparing test and control group (p> 0.05) after four years. Conclusion: The clinical performance-based resin silorane was similar to the methacrylate-based resin. The composite resin-based silorane could be a promising alternative for Class I restorations, based on a material like methacrylate-based clinical performance.